Is the use of green shopping bags gendered? Evidence from a gender equality conscious emerging market - Muposhi, Asphat; Mpinganjira, Mercy; Wait, Marius; Issock, Paul Blaise Issock (Inderscience, 2022)
This study examined whether the behaviour of using 'green' shopping bags varied according to gender in South Africa - a country known for promoting gender equality. The study's results revealed gender differences in the use of green shopping bags in respect of the new ecological paradigm, awareness of consequences, ascription of responsibility, attitude towards green shopping bags, intention to use green shopping bags and perceived behavioural control. The findings of this study underscore the importance of fostering the development of personal and descriptive norms related to the use of green shopping bags for both male and female consumers. If norms remain weak, it will be difficult to entrench the behaviour of using green shopping bags. The study also showed that the other key factors necessary for promoting the use of green shopping bags among both male and female consumers include inculcating pro-environmental beliefs, enhancing awareness of consequences plastic bag litter and fostering pro-environmental attitudes. The study's findings also highlight the urgent need to minimise the structural barriers associated with the use of green shopping bags, especially among female consumers. This could be done by making green shopping bags affordable through incentives or subsidies.